The Influence of Vertical Centrifugal Casting on Nickel Aluminum Bronze Alloy for Using in the Royal Thai Navy - Kengpol, Athakorn; Chanchittakarn, Chawantorn (Applied Science and Engineering Progress, 2021)
This research presents a guideline for forming nickel aluminum bronze or NAB workpieces in better mechanical properties for use in the Royal Thai Navy. In the past, NAB workpieces were formed by static casting and then were used in seawater condition, and it was found that the deterioration and low lifespan was a result of cavitation corrosion. Therefore, the analysis can be made that the mechanical properties are inappropriate for use in seawater conditions. This research discusses the advantages of the vertical centrifugal casting method on the static casting regarding the specimen’s hardness value. Therefore, the objective of this research is to study the influence of vertical centrifugal casting on hardness of NAB specimens using experimental design to determine appropriate conditions for NAB specimen’s hardness. The appropriate level of the mould speed is 483.8384 rounds per minute and the radius from centre of rotation is the 100 mm, and the result of the appropriate factors is 177.3542 VH as a maximum hardness. The regression equation from this research can also be used to form other appropriate mould speeds for other size of workpieces.